Investigation of RFID tag readability for pharmaceutical products at item level - Erdem, Ergin; Zeng, Hai; Zhou, Junyi; Shi, Jing; Wells, David L. (Drug development and industrial pharmacy, 2009)
Background: The applications of radio frequency identification (RFID) technology carry a tremendous potential for pharmaceutical industry. There is a pressing need to analyze the performance of RFID tags attached to various pharmaceutical dosage forms. Method: The readability of RFID-tagged pharmaceutical products is, for the first time, systematically investigated by experiments. Factors considered include dosage forms, ion concentration in solution, angle of rotation, and distance between the RFID tag and the interrogator. Results: Compared with empty container, the filling of any representative dosage forms causes deteriorated readability for the tag attached to container. Analysis of variance reveals that the effects of dosage forms, angle of rotation, and their interaction are statistically significant. In addition, an increase in distance (equivalent to higher RF attenuation level) and higher ion concentration in solution beyond a certain level have detrimental effect on tag readability. Conclusion: The analysis shows that the RFID tag readability is strongly dependent on the factors that are experimented with. The level of the factors for optimum RFID system performance should be adjusted based on the particular application.